Selfdirected learning: Status of finalyear students and perceptions of selected faculty leadership in a Nigerian medical school â€" a mixed analysis study - A Louw; T Nottidge (South African Medical Association, 2017)
Background. Self-directed learning (SDL) is the essential mechanism of lifelong learning, which, in turn, is required for medical professionals to maintaincompetency because of advancing technology and constantly evolving disease care and contexts. Yet, most Nigerian medical schools do not actively promote SDL skills for medical students.Objective. To evaluate the status of SDL behaviour among final-year students, and the perceptions of faculty leadership towards SDL in a Nigerian medical school.Methods. A mixed research method was used, with a survey consisting of a validated Likert-based self-rating scale for SDL (SRSSDL) to assess students’SDL behaviour. Focus group discussions with selected faculty leaders were thematically analysed to assess their perceptions of SDL.Results. The medical students reported moderate SDL behaviour, contrary to faculty, who considered their students’ SDL behaviour to be low. Faculty leadership further defined SDL as the self-motivated student demonstrating initiative in learning under the guidance of teachers, who use interactive forums for teaching. Furthermore, teachers and students should partner towards the goal of ensuring that student learning takes place. Teachers expressed concerns about SDL methods in medical schools owing to the fear that this will require medical students to teach themselves medicine without expert guidance from teachers.Conclusion. This study suggests that final-year students have a low to moderate level of SDL behaviour. The index faculty are willing to develop teacherguidedself-motivated learning for their students, rather than strict SDL. Faculty should be concerned about this behaviour and should encourage SDL in such a way that students realise its benefits to become lifelong learners. Further study of the perceptions about self-regulated learning are recommended.